Substantially increased electrical conductivity of polyaniline through blending with babassu oil in the presence of dichloromaleic anhydride - Borges, Fernando de M.; Cunha, Giovanni P. da; Dognani, Guilherme [UNESP]; Bacarin, Giovani B. [UNESP]; Cabrera, Flávio C. [UNESP]; Job, Aldo E. [UNESP]; Vega, Maria L.; Matos, José M.E.; Cunha, Helder N. da (Elsevier, 2019)
The development of new materials to be employed as active layer in organic semiconductor devices is a highly important research field. Alongside high performance, low cost and environmental safety are among the sought device characteristics. Previously the formation of PAni/Babassu polymer blends with interesting characteristics was reported. In the present work we report improvements on the electric conductivity of capacitor like devices employing Polyaniline (PAni) as active layer by the addition of dichloromaleic anhydride (DCM) during the synthesis of the Babassu-oil based polymer. FT-IR spectra confirm the occurrence of the reaction for the formation of the monoacylglyceride – MAG, the formation of the Polyanhydride (Polydichloromaleic anhydride – PDM) as well as the formation of the PAni/PDM blends. AFM images show that the presence of PDM changes the surface of the thin films, which become more uniform and homogeneous. The direct current (DC) conductivity of the thin films increases by five orders of magnitude as a consequence of a 30% increase in PDM concentration, ranging from ≈10−9 S/m for pure PAni to ≈ 10−4 S/m for the blend with 30% PDM. Impedance measurements at low electrical field frequency confirm these results; furthermore, the dependence of the complex impedance with the measurement's temperature indicate that the conduction processes are thermally activated. Two distinct conduction processes are present in the blends, as can be seen from the presence of two semi-circles in the complex-plane (Argand diagrams) representations. By employing a simple Havriliak-Negami model we obtained the characteristic relaxation time constants for both processes as a function of temperature, Arrhenius behavior was observed as a function of temperature for both processes.
Keywords: Babassu oil; Electrical conductivity; PAni/babassu; Polyanhydride